Morphogenesis of a late Pleistocene delta off the south-western Hainan Island unraveled by numerical modeling. (15th June 2020) - Zhang, Wenyan; Xiong, Ping; Meng, Qicheng; Dudzinska-Nowak, Joanna; Chen, Hui; Zhang, Han; Zhou, Feng; Miluch, Jakob; Harff, Jan
Graphical abstract: Highlights: A paleo-delta has been identified off SW Hainan Island. Dating results indicate a "normal regression" delta development that outpaced the sea level rise. Numerical modeling suggests two distinct transport pathways for the delta development. Convergence of sediment transport from both east and west coasts leads to delta formation. Abstract: A paleo-river delta off the south-western (SW) Hainan Island has been identified based on seismic and core evidence. Dating results suggest its initial development in 65 kyr BP during a global sea level lowstand ( 85 m below modern level) and termination in 56 kyr BP during a sea level highstand ( 50 m below modern level). Analysis of the delta internal architecture indicated a dominant offshore transport pathway from the SW Hainan Island. In order to unravel possible driving mechanisms for morphogenesis of the delta, 3-Dimensional numerical modeling was applied to investigate oceanographic and morphodynamic scenarios corresponding to the initial delta development. Results indicate that sediment dynamics in the study area is controlled by a compound effect of monsoon-driven circulation, river plumes, tides and typhoons. Contribution of the Red River to the delta development is smaller than local rivers in SW Hainan due to a combined effect by regional circulation and tides which causes a detour of the buoyancy-driven plume around the delta, despite of its larger runoff and sediment discharge compared to those from the local rivers of Hainan. On the other hand, simulation results suggest at least ten-times higher sediment supply rate from SW Hainan during the developing phase of the river delta than the modern condition. Such enhanced sediment supply might be caused jointly by 1) increased local river runoff from SW Hainan, and 2) alongshore transport from eastern Hainan which was connected to the main land during the sea level lowstand.